FACTORS INFLUENCING THE OCCURRENCE OF RHEUMATOID ARTHRITIS (RA) IN THE ELDERLY IN THE REGIONUPTDJAVA COMMUNITY HEALTH CENTER SIMALUNGUN DISTRICT YEAR 2020 - Pakpahan, Romauli; G. Maffett, Mark; Doortua, Doortua; Maswan, Maswan; Lubis, Josep (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease with the main manifestation of progressive polyathritis and involving organs throughout the body involved joints in patients with Rheumathoid Arthritis occur after the disease has progressed according to its progress is the number two disease that attacks the elderly in Indonesia. The factors that affect the occurrence of rheumatoid arthritis (RA) in the elderly in the UPTD Puskesmas Tanah Jawa, Simalungun regency in 2020 are prone to occur at the age of 44 years to 59 years and the age of 60 years up to 70 year. Patients with rheumatoid arthritis (RA) in the elderly mostly occurred in women with a total of 79 respondents (79.8%). According to (Lukman and Ningsih 2014),the occurrence of rheumatoid arthritis (RA) is due to hormonal disturbances (Estrogen) in the body of 99 elderly people, namely work activity factors which reached 61 people (61.8 %) and genetic factors amounted to 39 people (39.4%)